Urban climate change mitigation and adaptation planning: Are Italian cities ready?. (August 2019) - Pietrapertosa, Filomena; Salvia, Monica; De Gregorio Hurtado, Sonia; D'Alonzo, Valentina; Church, Jon Marco; Geneletti, Davide; Musco, Francesco; Reckien, Diana
Abstract: Climate Action Planning is one of the top priorities of cities in order to reduce greenhouse gas emissions and strengthening climate-resilience, as pointed out by the New Urban Agenda and the Paris Agreement. This study aims at assessing the development of climate change mitigation and adaptation planning in Italian cities. To this end, we analysed the availability of Local Climate Plans (LCPs) in 76 cities, which are included in the Eurostat Urban Audit (UA-2015) database. In a further step, we analysed the content of the urban climate change mitigation and adaptation plans available in a smaller sample of 32 Italian cities of 2007 Eurostat Urban Audit database (UA-3), looking at the single actions undertaken for addressing mitigation and adaptation to climate change. Results show the almost total absence of comprehensive and stand-alone urban climate change adaptation plans in Italy (except for two cities, Ancona and Bologna), whereas we found that in 61 out of 76 cities municipal civil protection plans are the instruments that deal with local emergencies associated to extreme weather events. On the other hand, 56 out of 76 urban climate change mitigation plans (i.e. Sustainable Energy Action Plans) are being developed in the framework of the Covenant of Mayors, which is a transnational network of local governments created by the European Union (EU) in 2012. The results obtained on the mitigation side point out that, in absence of a national law that imposes Italian cities to develop LCPs, transnational networks are an effective boost to voluntary commitment to reach EU climate and energy objectives. Highlights: The research shows a positive trend on urban climate change action in Italy. Italian cities are more focused on mitigation than to adaptation. Transnational networks have a crucial role in boosting climate planning in cities. Cities need to adopt a more holistic approach in dealing with climate change. More technical and financial resources are necessary to boost local climate actions.